Globalisation, health and culture: emerging issues. Proposals for an analysis from a social anthropology perspective - Palacios Ramírez, José; Rico Becerra, Juan Ignacio (Saúde e Sociedade, 2011)
The core proposal of this article is to present a series of reflections of a critical nature on the links between changes in the field of health care and processes of globalisation. A lot of our work is founded on our discipline of social anthropology; however, the theories of the French philosopher M. Foucault also play a central role in this paper. Our intention is that these reflections may contribute to subsequent debate among professionals in the social-health arena. The first part of this article talks about the challenge that supposes to think about the new social processes related to the health, due to the appearance of explanatory and interventional models, in which some aspects that we could denominate "cultural" seem to occupy a central place. Later, the text suggests, from a processual perspective, the emergent dynamics that could be taking the global medicalization processes of the life now, trying to point his paradoxes as the underflow of the traditional limits of the medical knowledges and the assemblage of new practices that they seem to translate to the medical field realities outside of his reach until now.